POLISEMI DALAM BAHASA ARAB - Dewi Ferawati (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Language in arabic has more than one meaning, so it is often confusing. When comunicating, certainly everyone uses vocabulary. Many of vocabulary words have been ascertained that the person often speaks. However, this situation influences on the development of language today. To know this, there needs to be deeper knowledge, about the use of words that are used more than one meaning and also know and understand the use of the same word but when someone says it gives a different meaning. A word is able to different meanings which is called polysemi. Polysemi is a lexeme that has multiple meanings. Because of the misunderstanding of such meaning, the listener or reader is hesitant to interpret the meaning of lexeme or the sentence he hears or reads.